2013
DOI: 10.1186/1754-6834-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Assembling a cellulase cocktail and a cellodextrin transporter into a yeast host for CBP ethanol production

Abstract: BackgroundMany microorganisms possess enzymes that can efficiently degrade lignocellulosic materials, but do not have the capability to produce a large amount of ethanol. Thus, attempts have been made to transform such enzymes into fermentative microbes to serve as hosts for ethanol production. However, an efficient host for a consolidated bioprocess (CBP) remains to be found. For this purpose, a synthetic biology technique that can transform multiple genes into a genome is instrumental. Moreover, a strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…To date, most studies have focused on the production of ethanol (for an overview of developments in various organisms, see recent reviews by Olson et al [2] and la Grange et al [3]). Recent examples of engineering for ethanol production via CBP via the native method include the production of 38.1 g/l ethanol from 92.1 g/l Avicel via a co-culture of modified Clostridium thermocellum and Thermoanaerobacterium saccharolyticum [4]; the ‘recombinant’ approach has recently generated strains of Saccharomyces cerevisiae [5] and Kluyveromyces marxianus [6] able to ferment hot water treated rice straw and Avicel respectively, although final ethanol titres were still low.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have focused on the production of ethanol (for an overview of developments in various organisms, see recent reviews by Olson et al [2] and la Grange et al [3]). Recent examples of engineering for ethanol production via CBP via the native method include the production of 38.1 g/l ethanol from 92.1 g/l Avicel via a co-culture of modified Clostridium thermocellum and Thermoanaerobacterium saccharolyticum [4]; the ‘recombinant’ approach has recently generated strains of Saccharomyces cerevisiae [5] and Kluyveromyces marxianus [6] able to ferment hot water treated rice straw and Avicel respectively, although final ethanol titres were still low.…”
Section: Introductionmentioning
confidence: 99%
“…gRNA integrated in Cas9-carrying yeast strain by PGASO. The six gRNA cassettes were together integrated into the selected Cas9-carrying strains using a modified PGASO technique 15,16 . We retained their own SNR52 promoters and SUP4 terminators in these gRNA cassettes.…”
Section: Ms Methods For Protein Identification and Analysismentioning
confidence: 99%
“…These six multiple genes were assembled into the genome of the host using PGASO technology. Experimental results indicated that the developed strain KR7 contains five recombinantly expressed heterologous cellulase genes and that strain could transform crystalline cellulose into ethanol (Chang et al, 2013).…”
Section: Development Of Consolidated Bioprocessing For Non-conventionmentioning
confidence: 99%